Waveguide antenna and method for forming metal layer on glass fiber reinforced plastic
By using mechanical roughening, expansion, concentrated sulfuric acid soaking and other processes on glass fiber reinforced plastic, the problem of poor roughness uniformity in the prior art is solved, and high bonding force and corrosion resistance between the metal layer and the plastic matrix are achieved. Performance, suitable for the production of high-frequency antennas.
Patent Information
- Application Number
- CN202411293750.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing process of forming a metal layer on glass fiber reinforced polyphenylene sulfide or polyetherimide plastic has poor roughness uniformity, which cannot meet the binding force requirements of the plating layer and the plastic matrix, affecting the reception or reflection signal of the antenna.
Mechanical roughening, expansion, concentrated sulfuric acid soaking, roughening, colloidal palladium activation, degluing, electroless plating and copper protection treatment are used to form a metal layer of specific roughness to enhance the bonding force between the metal layer and the plastic matrix.
Through this method, the bonding force between the metal layer and the plastic substrate is significantly improved, the production requirements of the waveguide antenna are met, and the corrosion-resistant copper protective layer is provided, which improves the sensitivity of the antenna.
Smart Images

Figure CN119194446A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of communication antennas, and in particular relates to a waveguide antenna and a method for forming a metal layer on a glass fiber reinforced plastic. Background Art
[0002] With the development of 5G / 6G technology and the continuous upgrading of wireless communication devices, high-frequency band antennas have increasingly higher requirements for the roughness of the coating on the plastic.
[0003] Polyphenylene sulfide (PPS) and polyetherimide (PEI) plastics are widely used in the production of antenna oscillators and waveguide antennas due to their excellent dielectric properties and low production costs. Polyphenylene sulfide (PPS) plastics and polyetherimide (PEI) plastics with added glass fiber (GF, referred to as glass fiber) have even better mechanical properties and heat resistance to achieve lightweight antennas.
[0004] At present, the metal layer is formed on glass fiber reinforced polyphenylene sulfide (PPS) plastic or polyetherimide (PEI) plastic, mostly by mechanical pre-roughening, roughening, neutralization, immersion, palladium activation, degumming, chemical plating and electroplating. However, this process has poor roughness uniformity and the roughness cannot meet the bonding requirements between the coating and the plastic substrate, which affects the antenna receiving or reflecting signals. Summary of the invention
[0005] In order to solve the deficiencies of the prior art, the present invention provides a method for forming a metal layer on a glass fiber reinforced plastic, by performing mechanical roughening, expansion, concentrated sulfuric acid soaking, roughening, colloidal palladium activation, debonding, chemical plating, electroplating and copper protection treatment on the substrate, thereby improving the bonding force between the metal layer and the plastic substrate, providing a metal layer with a specific roughness to meet the manufacturing requirements of the waveguide antenna. The present invention also provides a waveguide antenna manufactured by the method for forming a metal layer.
[0006] The technical effects to be achieved by the present invention are achieved through the following technical aspects:
[0007] In a first aspect, the present invention provides a method for forming a metal layer on a glass fiber reinforced plastic, comprising the following steps:
[0008] S1. An injection molded substrate, wherein the substrate has a surface, and the substrate is recessed in a direction away from the surface to form a cavity;
[0009] S2. Mechanical roughening treatment by sandblasting is performed on the substrate surface, followed by ultrasonic cleaning;
[0010] S3. Soak the mechanically roughened substrate in a swelling liquid to fully swell the surface plastic;
[0011] S4. The expanded substrate is immersed in a concentrated sulfuric acid solution;
[0012] S5. Soaking the substrate in the roughening liquid;
[0013] S6. Soaking the roughened substrate in a colloidal palladium solution to adsorb active palladium particles on the substrate surface; then soaking the colloidal palladium-activated substrate in a disintegration solution for disintegration treatment;
[0014] S7. The substrate after the debonding treatment is subjected to chemical nickel or copper plating to form an underlying metal layer of a nickel layer or a copper layer on the surface of the substrate;
[0015] S8. Electroplating copper on the substrate, electroplating copper on the bottom metal layer to form an intermediate copper layer;
[0016] S9. Perform copper protection on the middle copper layer to form a copper protection layer.
[0017] In some embodiments, the substrate is formed by injection molding of glass fiber reinforced polyphenylene sulfide or glass fiber reinforced polyetherimide plastic, and the surface layer of the substrate and the surface layer of the cavity together form the surface layer of the substrate.
[0018] In some embodiments, the mechanical roughening treatment in S2 uses brown corundum sand with a mesh size of 100-200 meshes, and according to the type of brown corundum sand, air sand blasting or water sand blasting is selected to form a mechanical roughening layer with a roughness of 0.4-2.0 μm on the surface of the substrate.
[0019] In some embodiments, the swelling fluid in S3 includes the following components:
[0020] Ether substances: 5-130g / L, sulfates: 10-120g / L, alcoholamine substances: 20-90g / L, and water.
[0021] In some embodiments, the soaking temperature in S4 is 20-35° C., the soaking time is 10-20 min, and the mass concentration of the concentrated sulfuric acid is 50-100%.
[0022] In some embodiments, the roughening solution in S5 includes the following components:
[0023] Nitric acid: 200-300ml / L, sulfuric acid: 50-300ml / L, fluoride-containing salts: 100-200g / L, surfactant: 0.1-0.3g / L, and water.
[0024] In some embodiments, the fluoride ion salt substance includes at least one of potassium fluoride, ammonium bifluoride and ammonium fluoride.
[0025] In some embodiments, the colloidal palladium solution in S6 includes the following components:
[0026] Pd 2+ : 12-30ppm, SnCl2: 3-10g / L, hydrochloric acid: 100-120ml / L, and water;
[0027] The degumming solution is a sulfuric acid solution with a mass concentration of 50-70 g / L.
[0028] In some embodiments, the thickness of the bottom metal layer in S7 is 0.2-0.5 μm; when the substrate is subjected to chemical nickel plating, an alkaline chemical nickel plating solution is used, which includes the following components:
[0029] Ni 2+ Content: 3-4g / L, hyposodium: 10-15g / L, and water;
[0030] The chemical nickel plating layer formed by the alkaline chemical nickel plating solution has a phosphorus content of 3-5%.
[0031] In some embodiments, the thickness of the intermediate copper layer in S8 is 5-15 μm; and the electroplating solution includes the following components:
[0032] Copper sulfate: 60-90g / L, sulfuric acid: 190-210g / L, chloride ion: 40-100mg / L, tank opener: 2-4ml / L, brightener: 1.5-3ml / L, and water.
[0033] In some embodiments, in S9, a copper protection liquid is used to form a copper protection layer on the middle copper layer; the copper protection liquid includes the following components:
[0034] Imidazole substances: 5-100 g / l, polyvinyl alcohol: 8-12 g / l, and water.
[0035] In some embodiments, the imidazole substance includes at least one of benzotriazole, sodium mercaptobenzothiazole or tolutriazole.
[0036] In a second aspect, the present invention further provides a waveguide antenna, which is manufactured by the above-mentioned method of forming a metal layer on a glass fiber reinforced plastic.
[0037] In summary, the present invention has at least the following benefits:
[0038] 1. The method for forming a metal layer on a glass fiber reinforced plastic provided by the present invention improves the bonding force between the metal layer and the plastic substrate by performing mechanical roughening, expansion, concentrated sulfuric acid immersion, roughening, colloidal palladium activation, degumming, chemical plating, electroplating and copper protection treatment on the substrate, thereby providing a metal layer with a specific roughness to meet the production requirements of the waveguide antenna.
[0039] 2. The method for forming a metal layer on a glass fiber reinforced plastic provided by the present invention, during the copper protection treatment, the copper protective agent and copper ions undergo chelation and chemical adsorption, thereby forming a dense and firm copper protective layer on the intermediate copper layer, thereby achieving corrosion resistance performance requirements.
[0040] 3. The present invention adopts a method of forming a metal layer on a glass fiber reinforced plastic to manufacture a waveguide antenna, which is more conducive to the manufacture of a high-frequency antenna and can effectively improve the sensitivity of the antenna. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 The figure is a flow chart of the method for forming a metal layer on a glass fiber reinforced plastic according to the present invention.
[0042] Figure 2 Schematic diagram of the phase structure of the substrate of Example 1 after mechanical roughening treatment.
[0043] Figure 3 Schematic diagram of the phase structure of the substrate of Example 1 after expansion and sulfuric acid immersion treatment.
[0044] Figure 4 Schematic diagram of the phase structure of the substrate of Example 1 after roughening treatment. DETAILED DESCRIPTION
[0045] For ease of understanding of the present invention, the present invention will be described more fully below in conjunction with specific examples and accompanying drawings. Preferred embodiments of the present invention are provided in the examples. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.
[0046] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0047] References in the specification to "one embodiment", "embodiment", "exemplary embodiment", etc. mean the embodiment being described, but not every embodiment may include a particular feature, structure, or characteristic. Specific features, structures, or characteristics are included. Moreover, such phrases do not necessarily refer to the same embodiment. In addition, when specific features, structures, or characteristics are described in conjunction with certain embodiments, whether or not explicitly described, it is within the knowledge of those skilled in the art to consider the effects of applying the features, structures, or characteristics to other embodiments.
[0048] The values expressed as ranges should be interpreted in a flexible manner, including not only the values explicitly listed as the limits of the range, but also all individual values or sub-ranges included in the range, as if each value and sub-range were clearly stated. For example, a (mass) concentration range of "about 0.1% to about 5%" should be interpreted as including not only the explicitly listed values of about 0.1% to about 5% by weight, but also the individual (mass) concentrations (e.g., 1%, 2%, 3% and 4%) and sub-ranges (e.g., 0.1% to 0.5%, 1.1% to 2.2% and 3.3% to 4.4%) within the specified range.
[0049] As described herein, unless stated otherwise, the terms "a" and "an" are used to include one or more than one, and the term "or" is used to refer to a non-exclusive "or". In addition, when a term or terms used herein are not otherwise qualified, they should be understood to be used for descriptive purposes only and not for limiting purposes. In addition, all publications, patents, and patent documents mentioned in the specification are incorporated herein by reference in their entirety, as if individually incorporated by introduction. If there is an inconsistency in usage between this document and those documents incorporated by reference, the usage in the cited references should be considered to supplement this document. For irreconcilable inconsistencies, the usage in this document shall prevail.
[0050] An embodiment of the present invention provides a method for forming a metal layer on a glass fiber reinforced plastic, which comprises the following steps:
[0051] S1. An injection molded substrate having a surface, and the substrate is recessed in a direction away from the surface to form a cavity;
[0052] S2. Mechanical roughening treatment by sandblasting is performed on the substrate surface, followed by ultrasonic cleaning;
[0053] S3. Soak the mechanically roughened substrate in a swelling liquid to fully swell the surface plastic;
[0054] S4. The expanded substrate is immersed in a concentrated sulfuric acid solution;
[0055] S5. Soaking the substrate in the roughening liquid;
[0056] S6. Soaking the roughened substrate in a colloidal palladium solution to adsorb active palladium particles on the substrate surface; then soaking the colloidal palladium-activated substrate in a disintegration solution for disintegration treatment;
[0057] S7. The substrate after the debonding treatment is subjected to chemical nickel or copper plating to form an underlying metal layer of a nickel layer or a copper layer on the surface of the substrate;
[0058] S8. Electroplating copper on the substrate, electroplating copper on the bottom metal layer to form an intermediate copper layer;
[0059] S9. Perform copper protection on the middle copper layer to form a copper protection layer.
[0060] In step S1 , the substrate is formed by injection molding of glass fiber reinforced polyphenylene sulfide or glass fiber reinforced polyetherimide plastic, and the surface layer of the substrate and the surface layer of the cavity together form the surface layer of the substrate.
[0061] Preferably, the matrix is formed by injection molding of 40% glass fiber reinforced polyphenylene sulfide plastic, that is, 40% by weight of glass fiber is added to polyphenylene sulfide plastic (PPS), and then injection molding is performed to obtain the matrix.
[0062] In step S2, the mechanical roughening treatment uses brown corundum sand with a mesh size of 100-200 meshes, and according to the type of brown corundum sand, air blasting or water blasting is selected to form a mechanical roughening layer with a roughness of 0.4-2.0 μm on the surface of the substrate, that is, the mechanical roughening layer has a uniform roughness.
[0063] After mechanical roughening, ultrasonic cleaning is performed to remove residual brown corundum sand and the like on the surface.
[0064] In step S3, the substrate after mechanical roughening and ultrasonic cleaning is immersed in an expansion liquid, wherein the expansion liquid includes the following components: ether substances: 5-130 g / L, sulfates: 10-120 g / L, alcoholamine substances: 20-90 g / L, and water.
[0065] The immersion conditions of the substrate in the swelling liquid are: immersion temperature: 20-60°C, immersion time: 5-20 minutes. Through immersion in the swelling liquid, the PPS or PEI in the plastic substrate is fully swollen, so that the surface layer can more fully contact and react with the subsequent roughening liquid.
[0066] In step S4, the expanded substrate is immersed in concentrated sulfuric acid with a mass concentration of 50-100%, the immersion temperature is 20-35°C, and the immersion time is 10-20 minutes. During the immersion process, the strong oxidizing property of high-concentration sulfuric acid is used to oxidize the phenyl sulfide groups (-C8H 11NO3S-) causes a certain degree of breakage, thereby generating some hydrophilic group acylamino (-CONH-).
[0067] In step S5, the roughening liquid for roughening the substrate includes the following components: nitric acid: 200-300 ml / L, sulfuric acid: 50-300 ml / L, fluorine-containing salt: 100-200 g / L, surfactant: 0.1-0.3 g / L, and water. Preferably, the fluorine-containing salt includes at least one of potassium fluoride, ammonium hydrogen fluoride, and ammonium fluoride.
[0068] The roughening conditions are as follows: soaking temperature: 25-30°C, soaking time: 12-25min.
[0069] After the matrix is expanded and soaked in sulfuric acid, the glass fiber is exposed from the surface of the matrix. During the roughening process, fluoride-containing salts (fluoride ion sources) provide fluoride ions to combine with H in the acid. + , reacting with the silicon atoms of the exposed glass fibers on the surface, causing the surface glass fibers to dissolve quickly and forming pits on the surface. At the same time, the nitric acid in the roughening solution reacts with the phenyl sulfide groups (-C8H 11 NO3S-) to oxidize and break it, generating a hydrophilic group acylamino (-CONH-).
[0070] In step S6, the roughened substrate is immersed in a colloidal palladium solution, wherein the colloidal palladium solution includes the following components: Pd 2+ : 12-30ppm, SnCl2: 3-10g / L, hydrochloric acid: 100-120ml / L, and water. The immersion conditions for colloidal palladium activation are: immersion temperature: 20-35°C, immersion time: 5-15min. Through colloidal palladium activation, a certain amount of active palladium particles are adsorbed on the substrate surface.
[0071] The substrate activated by colloidal palladium is immersed in a disintegration solution, which is a sulfuric acid solution with a mass concentration of 50-70g / L. The immersion conditions for the disintegration treatment are: immersion temperature: 20-45°C, immersion time: 50-82S. Through the disintegration treatment, the colloidal divalent tin around the palladium is removed, making the palladium more catalytically active.
[0072] In step S7, the substrate after the debonding treatment is subjected to chemical nickel or copper plating. When the substrate is subjected to chemical nickel plating, an alkaline chemical nickel plating solution is used, which includes the following components: Ni 2+ Content: 3-4g / L, hyponatremia: 10-15g / L, and water. The chemical nickel plating layer formed by the alkaline chemical nickel plating solution contains 3-5% phosphorus.
[0073] By chemically plating nickel or copper, a bottom metal layer of a nickel layer or a copper layer is formed on the surface of the substrate, and the thickness thereof is 0.2-0.5 μm. The chemical plating conditions are: bath temperature: 30-50°C, immersion time: 4-10 min.
[0074] In step S8, a 5-15 μm intermediate copper layer is electroplated on the bottom metal layer with a nickel layer or a copper layer chemically plated on the surface. The electroplating solution includes the following components: copper sulfate: 60-90 g / L, sulfuric acid: 190-210 g / L, chloride ion: 40-100 mg / L, tank opening agent: 2-4 ml / L, brightener: 1.5-3 ml / L, and water. The electroplating conditions are: bath temperature: 18-33°C, electroplating time: 10-30 min.
[0075] In step S9, a copper protection liquid is used to form a copper protection layer on the middle copper layer; the copper protection liquid includes the following components: imidazole substance: 5-100 g / l, polyvinyl alcohol: 8-12 g / l, and water.
[0076] Preferably, the imidazole substance includes at least one of benzotriazole, sodium mercaptobenzothiazole or tolutriazole.
[0077] During the copper protection treatment process, the copper protection liquid chelates with the active copper atoms or copper ions on the surface of the intermediate copper layer, and produces chemical adsorption to form a dense and strong copper protection film layer, which isolates the copper surface from oxygen in the air and protects the copper layer from corrosion.
[0078] It should be noted that after the processes of ultrasonic cleaning, expansion, concentrated sulfuric acid immersion, roughening, colloidal palladium activation, degumming, chemical plating, electroplating and copper protection treatment, water washing treatment is required respectively.
[0079] After the copper protective layer is formed in step S9, the finished product is washed, dried and inspected, and finally packaged.
[0080] Example 1
[0081] A waveguide antenna is prepared by forming a metal layer on a glass fiber reinforced plastic, the method comprising the following steps:
[0082] S1. A 40% glass fiber reinforced polyphenylene sulfide plastic injection molding matrix is used, wherein the matrix has a surface and a cavity, and the surface of the matrix and the surface of the cavity together form a surface layer.
[0083] S2. Mechanical roughening treatment is performed on the substrate surface by sandblasting, followed by ultrasonic cleaning.
[0084] like Figure 2As shown, after the mechanical roughening process by sandblasting, a mechanical roughening layer with a certain roughness is formed on the surface of the substrate. After testing, the roughness is 0.6 μm.
[0085] S3. Soak the mechanically roughened substrate in a swelling liquid to fully swell the plastic on the surface; the swelling liquid includes the following components: ether substance: 100g / L, sulfate: 20g / L, alcohol amine substance: 50g / L, and water. The swelling soaking conditions are: soaking temperature: 30°C, soaking time: 10min.
[0086] S4. Soak the expanded substrate in a concentrated sulfuric acid solution with a mass concentration of 90% at a temperature of 30° C. for 15 minutes.
[0087] like Figure 3 As shown in the figure, after the matrix is expanded and soaked in concentrated sulfuric acid, the strong oxidizing property of high-concentration sulfuric acid causes the phenyl sulfide groups (-C8H 11 NO3S-) causes a certain degree of breakage, thereby generating some hydrophilic group acylamino groups (-CONH-), which are rougher than the mechanically roughened layer after mechanical roughening treatment.
[0088] S5. Soak the substrate in a roughening solution; the roughening solution includes the following components: nitric acid: 200 ml / L, sulfuric acid: 100 ml / L, fluorine-containing salts: 100-200 g / L, surfactant: 0.1-0.3 g / L, and water. Fluorine-containing salts include potassium fluoride, ammonium hydrogen fluoride, and ammonium fluoride. The roughening conditions are: soaking temperature: 30°C, soaking time: 20 min.
[0089] During the roughening process, fluoride-containing salts provide fluoride ions to combine with H in the acid. + , reacting with the silicon atoms of the exposed glass fibers on the surface, causing the surface glass fibers to dissolve quickly and forming pits on the surface. At the same time, the nitric acid in the roughening solution reacts with the phenyl sulfide groups (-C8H 11 NO3S-) is oxidized to break it, producing a hydrophilic group acylamino (-CONH-), and its surface will appear rougher.
[0090] S6. Soaking the roughened substrate in a colloidal palladium solution to allow the substrate surface to adsorb active palladium particles; the colloidal palladium solution includes the following components: Pd 2+ : 20ppm, SnCl2: 5g / L, hydrochloric acid: 100ml / L, and water. The immersion conditions for colloidal palladium activation are: immersion temperature: 30°C, immersion time: 10min.
[0091] After that, the substrate activated by colloidal palladium is immersed in a disintegration solution for disintegration treatment. The disintegration solution is a sulfuric acid solution with a mass concentration of 60 g / L. The immersion conditions of the disintegration treatment are: immersion temperature: 30° C., immersion time: 60 seconds.
[0092] S7. Electroless nickel plating is performed on the substrate after the debonding treatment. The alkaline electroless nickel plating solution forms a bottom metal layer of a nickel layer on the surface of the substrate, and the thickness of the bottom metal layer is 0.3 μm. The alkaline electroless nickel plating solution includes the following components: Ni 2+ Content: 3g / L, hyponatremia: 15g / L, and water. Chemical plating conditions are: bath temperature: 300°C, immersion time: 10min.
[0093] S8. Electroplating copper on the substrate, electroplating copper on the bottom metal layer, forming a 10 μm intermediate copper layer. The electroplating solution includes the following components: copper sulfate: 70 g / L, sulfuric acid: 200 g / L, chloride ion: 50 mg / L, tank opener: 3 ml / L, brightener: 2 ml / L, and water. The electroplating conditions are: bath temperature: 30°C, electroplating time: 20 min.
[0094] S9. Use a copper protection solution to form a copper protection layer on the middle copper layer; the copper protection solution includes the following components: imidazole substance: 200 g / l, polyvinyl alcohol: 10 g / l, and water. The imidazole substance is sodium mercaptobenzothiazole.
[0095] Finally, after washing, drying and inspection, a substrate with a metal coating is obtained and a waveguide antenna is manufactured.
[0096] Example 2
[0097] A waveguide antenna is prepared by forming a metal layer on a glass fiber reinforced plastic. In the method, step S5 is adjusted as follows:
[0098] S5. Soak the substrate in a roughening solution; the roughening solution includes the following components: nitric acid: 200 ml / L, sulfuric acid: 100 ml / L, ammonium hydrogen fluoride: 100 g / L, potassium fluoride: 80 g / l, surfactant: 0.1-0.3 g / L, and water. The roughening conditions are: soaking temperature: 30°C, soaking time: 12 min.
[0099] The remaining steps are the same as those in Example 1.
[0100] Example 3
[0101] A waveguide antenna is prepared by forming a metal layer on a glass fiber reinforced plastic. In the method, step S5 is adjusted as follows:
[0102] S5. Soak the substrate in a roughening solution; the roughening solution includes the following components: nitric acid: 200 ml / L, sulfuric acid: 100 ml / L, ammonium hydrogen fluoride: 150 g / L, ammonium fluoride: 50 g / l, surfactant: 0.1-0.3 g / L, and water. The roughening conditions are: soaking temperature: 30°C, soaking time: 25 min.
[0103] The remaining steps are the same as those in Example 1.
[0104] Comparative Example 1
[0105] A waveguide antenna is prepared by forming a metal layer on a glass fiber reinforced plastic, the method comprising the following steps:
[0106] S1. A 40% glass fiber reinforced polyphenylene sulfide plastic injection molding matrix is used, wherein the matrix has a surface and a cavity, and the surface of the matrix and the surface of the cavity together form a surface layer.
[0107] S2. Mechanical roughening treatment is performed on the substrate surface by sandblasting, followed by ultrasonic cleaning.
[0108] S3. The substrate after ultrasonic cleaning is immersed in a colloidal palladium solution to adsorb active palladium particles on the surface of the substrate; the colloidal palladium solution includes the following components: Pd 2+ : 20ppm, SnCl2: 5g / L, hydrochloric acid: 100ml / L, and water. The immersion conditions for colloidal palladium activation are: immersion temperature: 30°C, immersion time: 10min.
[0109] After that, the substrate activated by colloidal palladium is immersed in a disintegration solution for disintegration treatment. The disintegration solution is a sulfuric acid solution with a mass concentration of 60 g / L. The immersion conditions of the disintegration treatment are: immersion temperature: 30° C., immersion time: 60 seconds.
[0110] S4. Electroless nickel plating is performed on the substrate after the debonding treatment. The alkaline electroless nickel plating solution forms a bottom metal layer of a nickel layer on the surface of the substrate, and the thickness of the bottom metal layer is 0.3 μm. The alkaline electroless nickel plating solution includes the following components: Ni 2+ Content: 3g / L, hyponatremia: 15g / L, and water. Chemical plating conditions are: bath temperature: 300°C, immersion time: 10min.
[0111] S5. Electroplating copper on the substrate, electroplating copper on the bottom metal layer, forming a 10 μm intermediate copper layer. The electroplating solution includes the following components: copper sulfate: 70 g / L, sulfuric acid: 200 g / L, chloride ion: 50 mg / L, tank opener: 3 ml / L, brightener: 2 ml / L, and water. The electroplating conditions are: bath temperature: 30°C, electroplating time: 20 min.
[0112] S6. Use a copper protection solution to form a copper protection layer on the middle copper layer; the copper protection solution includes the following components: imidazole substance: 100 g / l, polyvinyl alcohol: 10 g / l, and water. The imidazole substance is sodium mercaptobenzothiazole.
[0113] Finally, after washing, drying and inspection, a substrate with a metal coating is obtained and a waveguide antenna is made.
[0114] In Comparative Example 1, after the mechanical roughening treatment, the colloidal palladium activation treatment was directly performed without the swelling liquid soaking, the concentrated sulfuric acid soaking and the roughening treatment.
[0115] Comparative Example 2
[0116] A waveguide antenna is prepared by forming a metal layer on a glass fiber reinforced plastic, the method comprising the following steps:
[0117] S1. A 40% glass fiber reinforced polyphenylene sulfide plastic injection molding matrix is used, wherein the matrix has a surface and a cavity, and the surface of the matrix and the surface of the cavity together form a surface layer.
[0118] S2. Mechanical roughening treatment is performed on the substrate surface by sandblasting, followed by ultrasonic cleaning.
[0119] S3. Soak the mechanically roughened substrate in a swelling liquid to fully swell the plastic on the surface; the swelling liquid includes the following components: ether substance: 100g / L, sulfate: 20g / L, alcohol amine substance: 50g / L, and water. The swelling soaking conditions are: soaking temperature: 30°C, soaking time: 10min.
[0120] S4. Soak the expanded substrate in a concentrated sulfuric acid solution with a mass concentration of 90% at a temperature of 30° C. for 15 minutes.
[0121] S5. Soak the substrate in a roughening solution; the roughening solution includes the following components: nitric acid: 200 ml / L, sulfuric acid: 100 ml / L, fluorine-containing salts: 100-200 g / L, surfactant: 0.1-0.3 g / L, and water. Fluorine-containing salts include potassium fluoride, ammonium hydrogen fluoride, and ammonium fluoride. The roughening conditions are: soaking temperature: 30°C, soaking time: 20 min.
[0122] S6. Soaking the roughened substrate in a colloidal palladium solution to allow the substrate surface to adsorb active palladium particles; the colloidal palladium solution includes the following components: Pd 2+ : 20ppm, SnCl2: 5g / L, hydrochloric acid: 100ml / L, and water. The immersion conditions for colloidal palladium activation are: immersion temperature: 30°C, immersion time: 10min.
[0123] S7. Electroless nickel plating is performed on the substrate after the debonding treatment. The alkaline electroless nickel plating solution forms a bottom metal layer of a nickel layer on the surface of the substrate, and the thickness of the bottom metal layer is 0.3 μm. The alkaline electroless nickel plating solution includes the following components: Ni 2+ Content: 3g / L, hyponatremia: 15g / L, and water. Chemical plating conditions are: bath temperature: 300°C, immersion time: 10min.
[0124] S8. Electroplating copper on the substrate, electroplating copper on the bottom metal layer, forming a 10 μm intermediate copper layer. The electroplating solution includes the following components: copper sulfate: 70 g / L, sulfuric acid: 200 g / L, chloride ion: 50 mg / L, tank opener: 3 ml / L, brightener: 2 ml / L, and water. The electroplating conditions are: bath temperature: 30°C, electroplating time: 20 min.
[0125] Finally, after washing, drying and inspection, a substrate with a metal coating is obtained and a waveguide antenna is made.
[0126] Comparative Example 2 was not subjected to copper protection treatment.
[0127] Performance Testing
[0128] 100-grid test of coating: Use a 100-grid knife to draw 10*10 (100) 2MM*2MM small grids on the coating to be tested, and each line should be deep to the bottom layer of the coating: Use 3M250 adhesive tape to firmly stick the small grid to be tested, and use an eraser to wipe the tape hard. After leaving it for 5 minutes, pull one end of the tape hard, and quickly tear off the tape in the vertical direction (90°), and judge the coating shedding situation in the grid area.
[0129] 48hr neutral salt spray test: Test conditions: the temperature in the box is usually set at 35℃, the concentration of NaCl solution is 40-60g / l, the pH value of the solution is adjusted to the neutral range (6.5-7.2), the pressure in the saturated barrel is 1kgf, the spray volume is at any position in the working space, and a 80cm2 funnel is used to collect the salt spray precipitation after continuous atomization for 8h, and 1.6ml of solution is collected every hour; then the surface corrosion of the coating is tested under this continuous atomization for 48hrs, i.e. 48hrs test.
[0130] The performance test of the substrates with metal coatings prepared in Examples 1-3 and Comparative Examples 1-2 was carried out according to the above test method. The test results are shown in Table 1.
[0131] Table 1 Performance test results of the substrates with metal coatings prepared in Examples 1-3 and Comparative Examples 1-2
[0132] Test items Roughness RA / UM 100 grid test 48hr neutral salt spray test Example 1 0.60 5B OK Example 2 0.54 5B OK Example 3 0.64 5B OK Comparative Example 1 0.49 1B OK Comparative Example 2 0.60 5B NG
[0133] As shown in Table 1, compared with Comparative Example 1, the methods for forming a metal layer on a glass fiber reinforced plastic provided in Examples 1-3 prepare a substrate with a metal coating, and the bonding force between the metal layer and the plastic substrate is improved by performing mechanical roughening, expansion, concentrated sulfuric acid immersion, roughening, colloidal palladium activation, degumming, chemical plating, electroplating and copper protection treatments on the substrate, respectively, so as to provide a metal layer with a specific roughness to meet the manufacturing requirements of the waveguide antenna.
[0134] Compared with Comparative Example 2, during the copper protection treatment, the copper protective agent and copper ions undergo chelation and chemical adsorption to form a dense and firm copper protective layer on the intermediate copper layer, thereby achieving corrosion resistance performance requirements.
[0135] The above contents are merely examples and illustrations of the structure of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and these obvious replacement forms all belong to the protection scope of the present invention.
Claims
1. A method for forming a metal layer on a glass fiber reinforced plastic, characterized in that: The following steps are involved: S1. An injection molded substrate, wherein the substrate has a surface, and the substrate is recessed in a direction away from the surface to form a cavity; S2. Mechanical roughening treatment by sandblasting is performed on the substrate surface, followed by ultrasonic cleaning; S3. Soak the mechanically roughened substrate in a swelling liquid to fully swell the surface plastic; S4. The expanded substrate is immersed in a concentrated sulfuric acid solution; S5. Soaking the substrate in the roughening liquid; S6. Soaking the roughened substrate in a colloidal palladium solution to adsorb active palladium particles on the substrate surface; then soaking the colloidal palladium-activated substrate in a disintegration solution for disintegration treatment; S7. The substrate after the debonding treatment is subjected to chemical nickel or copper plating to form an underlying metal layer of a nickel layer or a copper layer on the surface of the substrate; S8. Electroplating copper on the substrate, electroplating copper on the bottom metal layer to form an intermediate copper layer; S9. Perform copper protection on the middle copper layer to form a copper protection layer.
2. The method for forming a metal layer on a glass fiber reinforced plastic according to claim 1, characterized in that: The matrix is formed by injection molding of glass fiber reinforced polyphenylene sulfide or glass fiber reinforced polyetherimide plastic, and the surface layer of the matrix and the surface layer of the cavity together form the surface layer of the matrix.
3. The method for forming a metal layer on a glass fiber reinforced plastic according to claim 1, characterized in that: In S2, the mechanical roughening treatment is to use brown corundum sand with a mesh size of 100-200 meshes, and according to the type of brown corundum sand, select air sand blasting or water sand blasting to form a mechanical roughening layer with a roughness of 0.4-2.0 μm on the surface of the substrate.
4. The method for forming a metal layer on a glass fiber reinforced plastic according to claim 1, characterized in that: In S3, the expansion fluid includes the following components: Ether substances: 5-130g / L, sulfates: 10-120g / L, alcoholamine substances: 20-90g / L, and water.
5. The method for forming a metal layer on a glass fiber reinforced plastic according to claim 1, characterized in that: In S4, the soaking temperature is 20-35° C., the soaking time is 10-20 min, and the mass concentration of the concentrated sulfuric acid is 50-100%.
6. The method for forming a metal layer on a glass fiber reinforced plastic according to claim 1, characterized in that: In S5, the roughening solution includes the following components: Nitric acid: 200-300ml / L, sulfuric acid: 50-300ml / L, fluoride-containing salts: 100-200g / L, surfactant: 0.1-0.3g / L, and water.
7. The method for forming a metal layer on a glass fiber reinforced plastic according to claim 6, characterized in that: The fluoride-containing salt substance includes at least one of potassium fluoride, ammonium hydrogen fluoride and ammonium fluoride.
8. The method for forming a metal layer on a glass fiber reinforced plastic according to claim 1, characterized in that: In S6, the colloidal palladium solution includes the following components: Pd 2+ : 12-30ppm, SnCl2: 3-10g / L, hydrochloric acid: 100-120ml / L, and water; The degumming solution is a sulfuric acid solution with a mass concentration of 50-70 g / L.
9. The method for forming a metal layer on a glass fiber reinforced plastic according to claim 1, characterized in that: In S7, the thickness of the bottom metal layer is 0.2-0.5 μm; when the substrate is subjected to chemical nickel plating, an alkaline chemical nickel plating solution is used, which includes the following components: Ni 2+ Content: 3-4g / L, hyposodium: 10-15g / L, and water; The chemical nickel plating layer formed by the alkaline chemical nickel plating solution has a phosphorus content of 3-5%.
10. The method for forming a metal layer on a glass fiber reinforced plastic according to claim 1, characterized in that: In the step S8, the thickness of the intermediate copper layer is 5-15 μm; and the electroplating solution includes the following components: Copper sulfate: 60-90g / L, sulfuric acid: 190-210g / L, chloride ion: 40-100mg / L, tank opener: 2-4ml / L, brightener: 1.5-3ml / L, and water.
11. The method for forming a metal layer on a glass fiber reinforced plastic according to claim 1, characterized in that: In S9, a copper protection liquid is used to form a copper protection layer on the middle copper layer; the copper protection liquid includes the following components: Imidazole substances: 5-100 g / l, polyvinyl alcohol: 8-12 g / l, and water.
12. The method for forming a metal layer on a glass fiber reinforced plastic according to claim 1, characterized in that: The imidazole substance includes at least one of benzotriazole, sodium mercaptobenzothiazole or tolutriazole.
13. A waveguide antenna, characterized in that The metal layer is prepared by the method for forming a metal layer on a glass fiber reinforced plastic as described in any one of claims 1 to 12.
Citation Information
Patent Citations
Environment-friendly and efficient brass passivating agent
CN104313564A
Copper and copper alloy dedicated metal surface treatment agent
CN104818479A
Process for improving compactness of selective metallized coating on surface of common plastic and improving preparation efficiency of coating
CN112725796A
Surface roughening method and metallization method of polyphenylene sulfide base material
CN114059050A
Plastic antenna oscillator and manufacturing method thereof
CN115786892A
